Strategic Reduction Method for Energy Input and CO2 Emissions: Direct Supply of Underground Seawater for Land-Based Aquaculture Systems in South Korea - Seungyeop Baek; Byungchil Jeon; Sebong Oh; Wontak Choi; Seunggi Choi; Yonmo Sung (Energies)
This study addresses the challenges of and opportunities for achieving the ambitious greenhouse gas emissions reduction target of the fishery sector of the Republic of Korea, set at 96% by 2030. We also focus on the current status of land-based aquaculture and underground seawater resource development, quantitatively compare energy inputs for land-based fish cultivation, and evaluate the potential of underground seawater to reduce CO2 emissions. Since 2010, 762 underground seawater boreholes have been developed, yielding a cumulative daily pumpage of 125,780 m3. Jeollanam-do was found to have the highest daily pumpage, with an annual energy requirement of 131,205,613 Mcal. Despite the fact that the energy demands for underground seawater are higher in some months, it provides a 22.6% reduction in total annual energy consumption compared to surface water. The use of underground seawater for heating or cooling resulted in a 24.1% reduction in the required input energy. However, energy requirements increase due to the relatively high surface water temperature in some regions and seasons. This study also highlights the utilization of underground seawater in heating or cooling surface water via indirect applications using geothermal heat pumps. This innovative research broadens the methods of greenhouse gas mitigation, particularly in the agriculture, livestock, and fisheries industries.